Großmaßstäbige Gletscherkartierung in den Alpen: Eine Bibliographie - Brunner, Kurt (ERDKUNDE, 1986)
For about a hundred years large-scale glacier maps have been made on the basis of accurate geodetic-topographical surveys as a means of glaciological research. The greater part of these maps from the earliest beginnings have shown Alpine glaciers. In the following paper a description of the production and purpose of these maps is given. Finally, a bibliography of about forty large-scale glaciers is presented arranged according to groups of mountains.